Synchronous Colon and Pancreatic Rosai-Dorfman Disease. Issue 3 (March 2021) - Noggle, Emily; Ortanca, Ibrahim; Clark, Ian; Yadak, Nour; Glazer, Evan S.
Rosai-Dorfman disease (RDD) is primarily a disease of massive lymphadenopathy and sinus histiocytosis. It has been documented across extranodal organ systems, but it rarely has been described in the gastrointestinal tract only. Here is the unique case of 2 primary extra-nodal masses found simultaneously in the pancreas and right colon of a patient without the classical concomitant lymphadenopathy. We also reviewed the literature and found 11 additional cases of pancreatic RDD. This is the first male case and 1 of only 2 cases of RDD presenting synchronously in 2 distinct locations within the gastrointestinal system. Furthermore, we discuss the potential use of fine needle aspiration (FNA) and core sample biopsies in confirming a diagnosis of RDD.